Gestión administrativa y su incidencia en el desempeño operativo de la unidad educativa melvin jones, cantón el empalme año 2023 - Castro Romero, Selena Dayanara (2025)
The project titled "Administrative Management and Its Impact on the Operational Performance of the Melvin Jones Educational Unit, El Empalme Canton" aimed to analyze the impact of administrative practices on the institution’s functioning and operational efficiency. Effective management directly influences the appropriate use of resources, the quality of educational services, and the strengthening of the school environment. A mixed-methods approach was employed, and the SERVQUAL model, adapted to the educational context, was used to assess the community’s perception across five dimensions: tangibility, reliability, responsiveness, empathy, and assurance. Data collection included surveys administered to 325 high school students (from 1st to 3rd year), semi-structured interviews with the principal, and focus groups with 9 teachers and 1 administrative staff member. The results showed that 64% of students felt safe within the institution, and 61% perceived empathy in their interactions with staff.